Effect of educational environments on nursing faculty members' perceptions regarding oral care. Issue 4 (11th December 2018) - Haresaku, Satoru; Kubota, Keiko; Miyoshi, Maki; Iino, Hidechika; Monji, Mayumi; Aoki, Hisae; Hidaka, Tsuyako; Sato, Yuka; Mori, Yuta; Yamada, Miyuki; Yoshikawa, Chizuko; Naito, Toru
Abstract: Aim: To investigate nursing faculty members' perceptions of oral care and to identify the effects of an educational environment on their perceptions. Methods: A cross‐sectional questionnaire regarding oral care was conducted at eight nursing schools in Japan. A total of 156 (71.6%) faculty members participated in this study. Their perceptions of oral care practice were compared by using a statistical analysis according to the length of work experience, teaching field, school, and facility setting (defined as whether the school had an affiliated hospital with a dental department). Results: Almost all of the faculty members were nurses and most were female. Almost all perceived that oral care was effective in the prevention of aspiration pneumonia and frailty. There were significant differences by teaching field in the nurses' perceptions regarding with whom they should collaborate to conduct oral care and there were significant differences by school in the nurses' perceptions regarding who should provide oral care, where it should be provided, and what kinds of knowledge are important for practice. Perceptions of low involvement in oral care were significantly associated with the schools having an affiliated university hospital with a dental department. Conclusion: There were different perceptions regarding oral care among nursing faculty members and their perceptions might have been affected by their educational environment. Therefore, it is suggested that oral care education should be standardized and nursing faculty members should standardize the curriculum regarding oral care for nursing students.